A high-fat (HF) diet induced oxidative stress and steatosis in the liver was prevented by Swertia chirayita powder supplementation by upregulating antioxidant enzyme activities in rats - Iffat Nowshin Ismail; Mirza Alimullah; S.M. Mufidul Islam; Shamima Sultana; Ishrat Jahan; Hridoy Chandra Ghosh; Khondoker Shahin Ahmed; Hemayet Hossain; Md Junaeid Rahman; Nasrin Akhter; Ferdous Khan; Mohammad Borhan Uddin; et al. (Food and Humanity, 2026)

From palm saps to their derived sugars: A systematic review on physicochemical composition - Rosnizam Ismail; Mohd Khairuddin Mohd Talib; Fadhilah Jailani; Khairil Anuar Jantan; Parlan Parlan; Adi Md Sikin (Food and Humanity, 2026)

Edible bivalves and gastropods as bioindicators of MP pollution: Contamination patterns, and environmental significance - Md. Hafijul Islam; Gift Samuel David; Fatima Zahra Tagri; Khadiza Nasrin; Mohtasim Fowad Jamee; Shahidur Rahman; Mohammad Tofsir Uddin Khan; Mohd Saifur Rahman; Jakia Fatema Bithi; Rochita Debnath; Suvadra Rani Das; Md. Ismail Hossain; et al. (Marine Pollution Bulletin, 2026)

Aloe vera powder bio-filled jute fiber epoxy composites with enhanced thermal stability and modified water absorption behavior - Md Mahadi Hassan Parvez; Md. Arafat Islam; Md. Ismail Hossain; Mamun Hasan; Md. Shariat Ulla Shuvo; Md. Shoyeb; A. S. M. Tauabur Rahman Mondal; M. Ahasan Habib (Next Research, 2026)

Morpho-phenological and biochemical responses of maize (Zea mays L.) to salinity stress - Siddhartha Kumar Roy; Progna Shil; Tusar Kanti Roy; Abdullah Al Kafi; Omar Kayess; Bikash Chandra Sarker; Md. Shafiqul Islam Sikdar; Md. Yasin Ali; Mohammed Ziauddin Kamal; Md. Saiful Islam; Zulhilmi Ismail (Journal of Crop Science and Biotechnology, 2026)

Large-scale microtremor analysis and lineament mapping for evaluating geological hazards in reservoir-induced seismicity regions: The case history of Kenyir Geopark - Susie Cahyanti Tasman; Neeran Niraj; Muhammad Noor Hisyam Jusoh; Abdul Halim Abdul Latiff; Siti Nur Fathiyah Jamaludin; Muhd Nur Ismail Abdul Rahman; Rudiyanto; Muhammad Afiq Md Ali; Muhamad Zaki Zulkifli; Yuzwan Mohamad; Kee Soo Chen; Fawwaz Azfar Abd Ghafar; et al. (Journal of Applied Geophysics, 2026)

Impacts of infrastructure development on taxonomic and functional diversity of non-volant small mammals - Ummi Nur Syafiqah Daud; Muhammad Iqbal Md. Jamaluddin; Nor Adibah Ismail; Nurfatin Batrisyia Md. Ali; Noor Fatihah Najihah Arazmi; Norfazliyana Nordin; Saiful Hilmi Jamal Shuhaily; Fudzla Zulfa Khiruddin; Amirul Haikal Zainal; Shukor Md. Nor; Aisah Shukor; Mohammad Saiful Mansor (Biodiversity and Conservation, 2026)

Microplastic contamination in locally and industrially produced organic fertilizers: Implications for sustainable agriculture and risk mitigation - Mahfuz Ahmmed; Md Hasibuzzaman; Ismail M. Rahman; Sadia Sultana Mitu; Tapos Kumar Chakraborty; Gopal Chandra Ghosh (Chemosphere, 2026)

Assessing reach and perceptions of hygiene behaviour change interventions for people with disabilities and older adults: Multi-country matched cross-sectional study - Kazy Farhat Tabassum; Dewan Muhammad Shoaib; Md. Assaduzzaman Rahat; Mehedi Hasan; Dani Barrington; Ben Tidwell; Lauren D'Mello-Guyett; Anjali Sharma; Sheillah Simiyu; Ismail Hosen; Jenala Chipungu; Fachruddin Mangunjaya; et al. (International Journal of Hygiene and Environmental Health, 2026)

Seroprevalence and risk factors of peste des petits ruminants virus in goats in border areas of Bangladesh - Ismail Hossain; Rupaida Akter Shila; Md Mohi Uddin; Md Jamilur Rahman; Md Rejaul Islam; Jahan Ara Begum; Rokshana Parvin; AKM Anisur Rahman; Emdadul Haque Chowdhury (Tropical Animal Health and Production, 2026)

AI in the international governance of land-based marine pollution: Legal frameworks and multilateral approaches - Md Syful Islam; Ismail Demir (Marine Policy, 2026)

NMR-based metabolomics of Indonesian jamu for diabetes: chemical composition, toxicity, and zebrafish behavioral impact - Muhammad Safwan Ahamad Bustamam; Wimbuh Tri Widodo; Mohd Zuwairi Saiman; Siti Munirah Mohd. Faudzi; Siok Geok Chong; Nur Diana Safura Mohd Ezmir; Emelia Asmara Md Daud; Sonny Kristianto; Intan Safinar Ismail (Natural Product Research, 2026)

Assessment of heavy metals and proximate composition of a jellyfish (Rhizostoma octopus Gmelin, 1791) from Cox's Bazar coast, Bay of Bengal, Bangladesh: Tracing contamination sources and human health risks - Md. Simul Bhuyan; Debasish Pandit; Mohammad Ismail; Mir Mohammad Ali; Md Khalid Saifullah; Md. Tarikul Islam; Ahmed Harun-Al-Rashid; Ummey Hafsa Bithi; Mrityunjoy Kunda; Md. Abu Bakar Siddique (Marine Pollution Bulletin, 2026)

Assessment of groundwater quality and human health risks using deterministic and probabilistic approaches in Chandina Upazila, Cumilla, Bangladesh - Md. Tahsinur Rahman; Mohammad Ismail; Sajib Ahmed; Sayed Abu Johany; Ajoy Deb Nath; Kanai Lal Das; Md Mozammel Haque; Mohammad Saiful Islam Bhuiyan (Environmental Geochemistry and Health, 2026)

Harnessing freshwater snails to enhance water quality and sustainability in integrated multi-trophic prawn farming systems, Bangladesh - Alif Layla Bablee; Mohammad Mahfujul Haque; Md. Mehedi Alam; Md. Zahid Hasan; Abdullah Al Rakib; Nusrat Jahan Tarin; Md. Ismail Hossain; Niels O. G. Jørgensen; Lars Hestbjerg Hansen (Molluscan Research, 2026)

Heavy metals in basic vegetables of the Bagerhat district, Bangladesh - Tusar Kanti Roy; Sudipta Kumar Nag; Md. Saiful Islam; Zulhilmi Ismail; Abubakr M. Idris (Food Additives & Contaminants Part B-Surveillance, 2026)

Atmospheric microplastics deposition in Dhaka City, Bangladesh: occurrence, distribution and ecological risk assessment - Md Tauhiduzzaman; Nishat Salsabil; Kobita Khatun; Md Muhaiminul Haque; Ahsan Habib; Mst Shamima Akter; Sojib Islam; Md Hasibuzzaman; Ismail M. Rahman; Mahfuz Ahmmed; Samina Zaman; Tapos Kumar Chakraborty; et al. (Atmospheric Pollution Research, 2026)

Prevention of Staphylococcus aureus biofilm formation on catheters, contact lenses, and contact lens cases by a synthetic analogue of the antimicrobial lipopeptide humimycin - Md Ramim Tanver Rahman; Ismail Fliss; Eric Biron (Biofouling, 2026)

Antidiabetic, antioxidant, and anti-inflammatory effects of Artemisia afra herbal infusion in iron-induced testicular injury - Huda Ismail; Almahi I. Mohamed; Md. Shahidul Islam (Natural Product Research, 2026)

Enhancing vibriosis vaccination in fish: genetically modified Nannochloropsis sp. as an oral vaccine carrier - Aisamuddin Ardi Zainal Abidin; Nor Izzati Husna Noorhisham; Fatimah Md Yusoff; Abdul Rahman Omar; Khatijah Yusoff; Saila Ismail; Mohd Ezuan Khayat; Murni Marlina Abd Karim; Ina Salwany Md Yasin; Chou Min Chong; Zetty Norhana Balia Yusof (World Journal of Microbiology and Biotechnology, 2026)

On the use of machine learning for the development of an acoustic-based detection system for early-stage thermal runaway - Wai Cheong Tam; MD. Ismail Siddiqi Emon; Jian Chen; Hongqiang Fang; Jun Deng; Anthony Putorti (Process Safety and Environmental Protection, 2026)

Fatty acid profile and bio-preservative efficacy of lactic acid bacteria postbiotics for improving microbiological safety in broiler meat - Md. Moklesur Rahman; Awis Qurni Sazili; Siti Aqlima Ahmad; Khalilah Abdul Khalil; Mohammad Rashedi Ismail-Fitry; Ayesha Shiddika Afsana; Md. Sazedul Karim Sarker (Food Control, 2026)

Emerging insights into low impact development (LID) strategy for urban flood resilience under climate change - Md Enamul Huq; David López-Carr; Nor Kalsum Mohd Isa; Hanifah Mahat; Mohd Hairy Ibrahim; Nasir Nayan; Mohamad Ihsan Muhamad Ismail; J. Jumadi; Md Kamrul Hossain; Md Nazirul Islam Sarker; Xijun Wu; Md Shouquat Hossain; et al. (Environmental Development, 2026)

Genomic characterization of Burkholderia glumae K6 and B. gladioli UPMBG7: causal agents of bacterial panicle blight in Malaysia - Adam Zafdri Md Zali; Siti Izera Ismail; Norsazilawati Saad; Muhammad Asyraf Md Hatta; Mohd Razi Ismail; Mohd Termizi Yusof; Mansor Hakiman; Syari Jamian; Sumaiyah Abdullah; Dzarifah Zulperi (European Journal of Plant Pathology, 2026)
Bacterial panicle blight (BPB), caused by Burkholderia glumae and B. gladioli , is a major threat to rice in Malaysia, with potential yield losses up to 75%. In June 2021, BPB symptoms were detected in Kedah rice fields. Isolates were identified through phenotypic traits, pathogenicity tests, and molecular analysis (16S rRNA and gyrB sequencing). Whole-genome sequencing of B. glumae K6 and B. gladioli UPMBG7 was performed using the Illumina NovaSeq 6000 platform. The assembled draft genome of B. glumae K6 contained 210 contigs, with a total genome size of 6.57 Mbp, 68.33% G + C content, and 5,641 coding sequences (CDS). It harbored toxoflavin biosynthesis genes ( toxABCDE , toxJ ) and a Type III secretion system (T3SS), contributing to its pathogenicity. B. gladioli UPMBG7 contained 124 contigs, with a total genome size of 8.22 Mbp, G + C content of 67.99, and 7,022 coding proteins. B. gladioli lacked the toxI gene for toxoflavin production but compensated with pyoverdine siderophore genes ( pvdA ), which facilitate iron acquisition. These findings highlight divergent infection mechanisms, with B. glumae relying on toxoflavin-mediated virulence and B. gladioli on resource competition. The genomic insights support the development of resistant rice cultivars, biological controls, and molecular diagnostics to improve BPB management in Malaysia.

Characterization of aquifer hydraulics and pumping well yield for supplemental paddy crop irrigation using pumping tests in Perak, Malaysia - Naseem Akhtar; Muhammad Izzuddin Syakir; Syahidah Akmal Muhammad; Aznan Fazli Ismail; Mohamad Shaiful Md. Yusuff; Leila Bouida; Hamza Mohamed Flafel; Pahmi Husain; Mohammed Benaafi; Taskin Ahmed; Mohammad Muqtada Ali Khan (Paddy and Water Environment, 2026)

Assessing habitat risks of mangrove species in the sundarbans: A cloud-based earth observation and invest HRA approach - Ismail Mondal; SK Ariful Hossain; Prasanta Roy; Felix Jose; Mohamed Mohamed Ouda; Sk Md Abu Imam Saadi; Lal Mohammad; Mukhiddin Juliev; Tarun Kumar De; Abdulrazak H. Almaliki (Environment, Development and Sustainability, 2026)

Heavy metal contamination in sediment of mudskipper habitat along the Cox’s Bazar coast, Bay of Bengal, Bangladesh: Ecological and human health risk assessment using deterministic and probabilistic approaches - Md. Simul Bhuyan; Mohammad Ismail; A.J.M. Morshed; Md. Tariqul Islam; Vinmoy Mondal (Regional Studies in Marine Science, 2026)

Effects of soil and water physicochemical characteristics under different anthropogenic disturbances on Pteroptyx firefly (Coleoptera: Lampyridae) populations in riparian habitats of Peninsular Malaysia - Nur Athirah Abdullah; Nurul Akmar Hussin; Nor Bazilah Razali; Lailatul-Nadhirah Asri; Hani Kartini Agustar; Shahril Mod Husin; Aisah Md. Shukor; Nurul Darsani Ahmad Darbis; Kamaruzzaman Ismail; Norela Sulaiman; Izfa Riza Hazmi (Journal of Insect Conservation, 2026)

Phytochemical investigation of Calophyllum sundaicum P.F.Stevens: isolation, structure elucidation, and biological potential - Mas Atikah Lizazman; Vivien Yi Mian Jong; Nor Hisam Zamakshshari; Yiizamy Suffian; Mohamad Izwan Bin Ismail; Enis Nadia Md Yusof; Nurr Maria Ulfa Binti Seruji (Natural Product Research, 2026)

Water quality and pollution dynamics in the Padma River, Bangladesh: Characterization of microbiological and chemical contaminants - Mohammad Kamruzzaman; Md. Nayeem; Mohammad Ismail; Md Firoz Khan; Sharmin Zaman Emon; Anowar Hosen; Asma Rahman; Muhammad Nurul Huda (Regional Studies in Marine Science, 2026)

Assessing the influence of shoreline proximity and anthropogenic activities on surface seawater quality in the coastal area of Port Dickson, Straits of Malacca, Malaysia - Nur Amiera Kamarudin; Ferdius Mohamat Yusuff; Ahmad Ismail; Fatimah Md. Yusoff (Regional Studies in Marine Science, 2026)

Tracing surface-adhered and internalized microplastics in leafy vegetables across urban and rural agroecosystems: Occurrence, characteristics, pollution indices, and exposure assessment - Ismail M. Rahman; Gopal Chandra Ghosh; Sadia Sultana Mitu; Mahfuz Ahmmed; Md Hasibuzzaman; Danisha Sultana; Jarin Tasnim Asha; Sojib Islam; Md. Tauhiduzzaman; Tapos Kumar Chakraborty; Samina Zaman; Seiya Hanamoto; et al. (Journal of Hazardous Materials, 2026)

Assessing trace metal based human health risks in the highly consumed vegetables collected from the industrialized zones of Bangladesh - Ummeh Sadia; Md. Nazrul Islam; Md. Ashraful Hoque; Taznova Anwar Tanbi; S. M. Ashraful Abedin Asha; Sabbir Howlader; Nobonita Sarker; Shahidul Islam; Ismail Rahman; Amitava Bandyopadhyay; Sumon Ganguli (Environmental Geochemistry and Health, 2026)

Assessing heavy metals toxicity in marine bed sediments of the Bay of Bengal: A novel baseline study on geochemical speciation, source, and risks - Md. Saiful Islam; Nor Aida Mahiddin; Debolina Halder Hemy; Abdullah Al Bakky; Uttam Biswas Antu; Zulhilmi Ismail; Nusrath Jahan Dristy; Tusar Kanti Roy; Mahmudul Hasan; Khalid A. Ibrahim; Abubakr M. Idris (Marine Pollution Bulletin, 2025)

Molecular characterization, pathology and innate cytokine responses associated with fowl adenovirus 8b in commercial chicken flocks in Bangladesh - Md. Riabbel Hossain; Shadia Tasnim; Most. Shahana Akter; Ismail Hossain; Győző L. Kaján; Lilla K. Máté; László Kőrösi; Emdadul Haque Chowdhury; Rokshana Parvin (The Veterinary Journal, 2025)

Comparative assessment of main roadside and sub roadside plantations on urban ecosystem functions in Dhaka North and South City areas of Bangladesh - Sumaiya Akter; Kazi Md Abu Sayeed; Naznin Parvin; Mahbuba Jamil; Hossain Md Dalim; Minhazul Kashem Chowdhury; Md. Ismail Hossain; Shuvramoy Mahato; Sanjida Abedin Prokriti; Sagoti Islam; Xiang Zhang; Pongpet Pongsivapai; et al. (Urban Ecosystems, 2025)

Characterizing Tropical Cyclone from Altimeter Wind Speed Profile - Nik Raisyha Nurfarain Abdullah; Syarawi M. H. Sharoni; Mohd Nadzri Md Reba; Hwee San Lim; Nurul Najwa Ayob; Ismail Ahmad Abir; Muhammad Zahir Ramli (Marine Geodesy, 2025)

Comprehensive assessment of marsh soil health index in beel aquaculture systems of coastal Bangladesh - Fariha Farzana; Tusar Kanti Roy; Mir Mohammad Ali; Sk Arafat Hossain; Rituparna Ghosh; Tatia Biswas; Mahjabin Mazrin; Jayosri Roy Jayoti; Bikash Chandra Sarker; Abu Shamim Khan; Md. Tanvir Anjum; Zulhilmi Ismail; et al. (Aquaculture International, 2025)

Microplastic toxicity in fish: A potential review on sources, impacts, and solution - Md. Towhidul Islam; Uttam Biswas Antu; Md. Shifat Hossain; Joyti Rani Paul; Tahsin Hasan; Pronayan Singha; Sandip Mitra; Sk Md Shoib Hasan; Zulhilmi Ismail; Md. Saiful Islam; Taher Sahlabjii; Abubakr M. Idris (Aquatic Toxicology, 2025)

Assessment of trace element contamination and human health risk in unrefined sea salt from Chattogram and Cox's Bazar, Bangladesh - Mohammad Ismail; Sajid Ibne Jamalfaisal; Md. Tahsinur Rahman; Sayed Abu Johany; Iasmin Akter; Sajib Ahmed (Environmental Geochemistry and Health, 2025)

Recent advances in layered double hydroixdes@MXene (LDHs@MXene) composites: Synthesis, properties, and catalytic applications - Sundas Riaz; Sami Ullah; Sanam Bashir; Aziz ur Rehman; Rashid Iqbal; Tayyaba Najam; Mostafa A. Ismail; Md Rezaul Karim; Syed Shoaib Ahmad Shah; Muhammad Altaf Nazir (Applied Clay Science, 2025)

Isolation and identification of rhizobacteria from Ludwigia octovalvis for degradation of polyethylene - Islam J.K. Elhabil; Siti Rozaimah Sheikh Abdullah; Hassimi Abu Hasan; Ahmad Razi Othman; Nur 'Izzati Ismail; Noorashikin Md Saleh (Algal Research, 2025)

Multicompartmental monitoring and associated health risks estimation of some selected pesticides in the aquatic ecosystems of Sungai Besar, Sekinchan, Malaysia - Md Ariful Islam; S. M. Nurul Amin; Dania Aziz; Mohd Fadhil Syukri Ismail; Christopher L. Brown; Abdul Shukor Juraimi; Md Abdul Halim; Md Kamal Uddin; Yahia Mahmud; Md Lifat Rahi; Aziz Arshad (Environmental Science and Pollution Research, 2025)

Assessing Heavy Metals using ICP-MS in Fruits from the Developing World and their Associated Health Risks - Tusar Kanti Roy; Sk Arafat Hossain; Md. Saiful Islam; Md. Fuad Hasan; Mahjabin Mazrin; Bikash Chandra Sarker; Zulhilmi Ismail; Khalid A. Ibrahim; Abubakr M. Idris (Biological Trace Element Research, 2025)

Evaluation of methanolic extracts from five important medicinal plants: Phytochemical profiling, antioxidant capacity, in vitro antidiabetic activity, and cytotoxicity assay - Md. Shakil Ahmed; Md. Taohid Hasan; Reaz Ahmmed; Md. Bismillah; M. Matiar Rahman; Mohammad Ismail Hossain; Masudul Hasan Khan; Mohammad Amirul Islam (South African Journal of Botany, 2025)

Production of cellulose nanocrystal (CNC) from papaya tree stem as a potential reinforcement in bionanocomposite manufacturing - Md. Mahmudur Rahman; Md. Ismail Hossain; Md. Elius Hosen Pk; Md. Al-amin; Salah Knani; Md. Waliullah; Md. Abdul Gafur; Bijoy Chandra Ghos (Bioresource Technology Reports, 2025)

Production of cellulose nanocrystals from the residual mass of P. chaba stem after methanol extraction as potential reinforcement in sustainable nanocomposite manufacturing: A cutting-edge approach in waste management - Md. Elius Hosen Pk; Md. Mahmudur Rahman; Bijoy Chandra Ghos; Nazim Uddin Ahmed; Md. Nakib Hossen; Salah Knani; M. Safiur Rahman; Md. Ismail Hossain (Bioresource Technology Reports, 2025)

Exogenous Application of ZnO Nanoparticles (NPs) To Palliate Salinity Induced Oxidative Stress in Lettuce (Lactuca Sativa L.) Plant - Tusar Kanti Roy; Md. Saiful Islam; Uttam Biswas Antu; Mousumi Jahan Sumi; Israt Jahan Irin; Sk Arafat Hossain; Keya Akter; Mahjabin Mazrin; Nor Aida Mahiddin; Habiba Zannat Meem; Abdullah Al Bakky; Zulhilmi Ismail; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Neuroprotective Effects of Cucurbita pepo Extract in Cuprizone-Induced Multiple Sclerosis Animal Model - Mohamed Rahamathulla; Rupesh Kumar; Yazan AlRashdan; Madhura M. Bose; Arumugam Muthukumar; Md Salahuddin; Mohammed Muqtader Ahmed; Thippeswamy Boreddy Shivanandappa; Ismail Pasha (Molecular Neurobiology, 2025)

A baseline toxicity assessment of sediment geochemistry, potentially toxic elements contamination, and ecological risk in sediment profiles of the Bay of Bengal coast, Bangladesh - Md. Saiful Islam; Abdullah Al Bakky; Nor Aida Mahiddin; Md. Towhidul Islam; Uttam Biswas Antu; Zulhilmi Ismail; Tusar Kanti Roy; Mahmudul Hasan; Kazi Aminul Islam; Avijit Sarkar; Khalid A. Ibrahim; Abubakr M. Idris (Regional Studies in Marine Science, 2025)

Pharmacological Potential of Holothuria (Mertensiothuria) leucospilota (Brandt, 1835): Antibacterial Activity Against Methicillin-Resistant Staphylococcus aureus and Metabolite Profile - Abdoulie Ceesay; Muhammad Farhan Nazarudin; Norfarrah Mohamed Alipiah; Ina Salwany Md Yasin; Mohammad Noor Azmai Amal; Mohamad Azzam Mohd Sayuti; Intan Safinar Ismail; Mohammed Aliyu-Paiko (Thalassas: An International Journal of Marine Sciences, 2025)

Analysis of respirable silica and heavy metals with their morphology in ambient air of Dhaka City - Mishuk Biswas; Md Ismail Hossain; AKM Khairul Bashar; Md Moniruzzaman; Abdus Salam; Md Safiqul Islam (Journal of Atmospheric Chemistry, 2025)

Preliminary Assessment of Essential and Potentially Toxic Elements in the Most Common Spices in a Developing Country: Health Hazard Implication - Md. Saiful Islam; Uttam Biswas Antu; Ruma Akter; Md. Shifat Hossain; Sujat Ahmed; Tusar Kanti Roy; Zulhilmi Ismail; Abubakr M. Idris (Biological Trace Element Research, 2025)

MicroRNA-122 regulates inflammatory and autophagic proteins by downregulating pyruvate kinase M2 in non-alcoholic fatty liver disease - Md Musa Hossain; Amit K. Mishra; Ajay K. Yadav; Akanksha; Md Ismail; Teja Naveen Sata; Amrendra K. Sah; Abdullah Al Mohit; Senthil K. Venugopal (Molecular and Cellular Biochemistry, 2025)

Occurrence of trace elements in water, fish and shellfish from estuarine and coastal areas of the east coast of Bangladesh, northeast Bay of Bengal: Human health risk implications - Seema Rani; Md. Kawser Ahmed; Chen Keliang; Kazi Belayet Hossain; Abu Hena Md. Yusuf; K.M. Azam Chowdhury; Md. Habibullah-Al-Mamun; Makidul Islam Khan; Nor Aida Mahiddin; Zulhilmi Ismail; Md. Saiful Islam (Marine Pollution Bulletin, 2025)

Bioaugmentation of Klebsiella pneumoniae isolate M1 in a continuous sequential phytoreactor integrating Scirpus grossus and Eichhornia crassipes plants for batik effluent treatment - Nurull Muna Daud; Siti Rozaimah Sheikh Abdullah; Siti Shilatul Najwa Sharuddin; Ahmad Razi Othman; Hassimi Abu Hasan; Noorashikin Md Salleh; Nur ’Izzati Ismail (Journal of Water Process Engineering, 2025)

Recent advances in recycling and upcycling of hazardous plastic waste: A review - Siti Zulaika Khairul Anuar; Abu Hassan Nordin; Siti Muhamad Nur Husna; Abdul Hafidz Yusoff; Syafikah Huda Paiman; Siti Fadilla Md Noor; Muhammad Luqman Nordin; Siti Nurlia Ali; Ya Mohammad Nazir Syah Ismail (Journal of Environmental Management, 2025)

A state-of-the-art review focusing on the fabrication technique of activated chitosan-bitumin coal based multifunctional bionanocomposites for industrial wastewater treatment: Production, characterization, and fixed bed column adsorption study - Md. Mahmudur Rahman; Md. Ismail Hossain; Bijoy Chandra Ghos; Md. Jasim Uddin; Salah Knani; Md. Waliullah (Journal of Environmental Chemical Engineering, 2025)

Dietary shifts in Barn Swallow Hirundo rustica passage and wintering in Peninsular Malaysia: From the early to late migratory season - Nor Adibah Ismail; Ummi Nur Syafiqah Daud; Noor Fatihah Najihah Arazmi; Shukor Md Nor; Mohammad Saiful Mansor (European Journal of Wildlife Research, 2025)

ALR inhibits HBV replication and autophagosome formation by ameliorating HBV-induced ROS production in hepatic cells - Amit Kumar Mishra; Md. Musa Hossain; Teja Naveen Sata; Kishor Pant; Ajay K. Yadav; Amrendra Kumar Sah; Parul Gupta; Md Ismail; Baibaswata Nayak; Shalimar; Senthil Kumar Venugopal (Virus Genes, 2025)

Assessment of the groundwater quality of the jessore municipality by using weighted arithmetic water quality index - Md Nahid Ferdous; Mojammel Hoque; Samsunnahar Popy; Mohammad Ismail Hossain; Rafiqul Islam Munna (Next Research, 2025)

A Comprehensive Assessment of Health Risks Associated with Heavy Metal Through Ingestion of Two Predominant Fish Species in a Developing Country - Tusar Kanti Roy; Sudipta Kumar Nag; Uttam Biswas Antu; Sk Arafat Hossain; Abdullah Al Bakky; Md. Tanvir Anjum; Bikash Chandra Sarker; Md. Rahamat Ullah; Fariha Farzana; Nor Aida Mahiddin; Ashish Biswas; Pronayan Singha; et al. (Biological Trace Element Research, 2025)

Application of Nanoparticles (NPs) to Ameliorate Abiotic Stress in Economically Important Crop Species: a Potential Review - Tusar Kanti Roy; Md. Saiful Islam; Nor Aida Mahiddin; Sk Arafat Hossain; Tatia Biswas; Uttam Biswas Antu; Sharmin Akter Serity; Jannatul Ferdawsi Miti; Sonia Akter; Smaranika Roy; Ashish Biswas; Mahjabin Mazrin; et al. (Journal of Crop Health, 2025)

Dust over Saudi Arabia from multisource data: case studies in winter and spring - Mazen E. Assiri; M. Nazrul Islam; Md Arfan Ali; Arjan O. Zamreeq; Ayman S. Ghulam; Muhammad Ismail (Air Quality, Atmosphere & Health, 2025)

Emerging technologies for efficient water use in agriculture: A review of current trends and future directions - Uttam Biswas Antu; Md. Saiful Islam; Sujat Ahmed; Md. Arifuzzaman; Sawmitra Saha; Puja Rani Mitu; Aditya Raj Sarkar; Nor Aida Mahiddin; Zulhilmi Ismail; Khalid A. Ibrahim; Abubakr M. Idris (Journal of Water Process Engineering, 2024)

Fabrication of CNC-AC bionanosorbents from the residual mass of Magnolia champaca l. Bark after methanol extraction for wastewater treatment: Continuous column adsorption study - Md. Mahmudur Rahman; Md. Ismail Hossain; Bijoy Chandra Ghos; Md. Abdul Gafur; Md.Ashraful Alam; Md. Jasim Uddin; Mst. Sarmina Yeasmin; Mehedi Hasan; Tahmina Akter Chowdhury; G.M. Masud Rana; Adity Karmakar; Jaytirmoy Barmon (Environmental Nanotechnology, Monitoring & Management, 2024)

The Novel Study On Arsenic Contamination, Health Risk, and Approaches to Its Mitigation From Water Resource of a Developing Country: A potential review - Md.Saiful Islam; Abdullah Al Bakky; Abu Reza Md. Towfiqul Islam; Mir Mohammad Ali; Md. Towhidul Islam; Zulhilmi Ismail; Md. Tanvir bin Hossain; Sujat Ahmed; Khalid A. Ibrahim; Abubakr M. Idris (Water, Air, & Soil Pollution, 2024)

Potentially toxic elements (PTEs) in the invasive Asian clam (Corbicula fluminea) from polluted urban river areas of Bangladesh and evaluation of human health risk - Md Muzammel Hossain; Shunkai Wang; Zhe Liang; Alei Geng; Iffat Jahan; Sunjida Jahan Tripty; Stephen J. Maxwell; Ismail Hossain; Sivasamy Sethupathy; Daochen Zhu (Environmental Monitoring and Assessment, 2024)

Toxicity assessment of heavy metals translocation in maize grown in the Ganges delta floodplain soils around the Payra power plant in Bangladesh - Md Saiful Islam; Abdullah Al Bakky; Sujat Ahmed; Md Towhidul Islam; Uttam Biswas Antu; Md Sadik Mahmud Saikat; Ruma Akter; Tusar Kanti Roy; Yeasmin Nahar Jolly; Kazi Aminul Islam; Avijit Sarkar; Zulhilmi Ismail; et al. (Food and Chemical Toxicology, 2024)

Toxicity factors, ecological and health risk assessments of heavy metal in the urban soil: a case study of an agro-machinery area in a developing country - Md. Saiful Islam; Abdullah Al Bakky; Md. Sadik Mahmud Saikat; Uttam Biswas Antu; Ruma Akter; Tusar Kanti Roy; Zulhilmi Ismail; Khalid A. Ibrahim; Abubakr M. Idris (Environmental Geochemistry and Health, 2024)

Trace element contamination in water and sediment in an estuarine ecosystem connected to the Bay of Bengal: A preliminary assessment of ecological and human health risks - Arnob Ghosh; Kowshik Das Karmaker; Mahmudul Hasan; Mahfujur Rahman; Nusrat Jahan Shimu; Md. Saiful Islam; M. Safiur Rahman; Md. Shawon Hossain; Zulhilmi Ismail (Marine Pollution Bulletin, 2024)

A review on sustainable graphene production from rice husks: Strategies and key considerations - Faten Ermala Che Othman; Nik Abdul Hadi Md. Nordin; Norafiqah Ismail; Hazirah Syahirah Zakria; Hazlina Junoh; Mohd. Haiqal Abd. Aziz (Chemical Engineering Journal, 2024)

Recent advances of MXene@MOF composites for catalytic water splitting and wastewater treatment approaches - Samreen Afzal; Aziz ur Rehman; Tayyaba Najam; Ismail Hossain; Mostafa A.I. Abdelmotaleb; Sundas Riaz; Md Rezaul Karim; Syed Shoaib Ahmad Shah; Muhammad Altaf Nazir (Chemosphere, 2024)

Exploring phosphate impact on arsenate uptake and distribution in freshwater phytoplankton: Insights from single-cell ICP-MS - Md Shah Alam; Kuo H. Wong; Akari Ishikawa; Meng Li; Yinghan Zai; Rimana Islam Papry; Asami S. Mashio; Ismail M.M. Rahman; Hiroshi Hasegawa (Chemosphere, 2024)

Strengthening education and training programmes for medical physics in Asia and the Pacific: the IAEA non-agreement technical cooperation (TC) regional RAS6088 project - Noriah Jamal; Anchali Krisanachinda; Virginia Tsapaki; Md Rafiqul Islam; Supriyanto Pawiro; Muhammad Al Omari; Chai Hong Yeong; Thinn Thinn Myint; Muhammad Basim Kakakhel; Mohammad Hassan Kharita; Cheow Lei James Lee; Anas Ismail; et al. (Physical and Engineering Sciences in Medicine, 2024)

A potential toxicological risk assessment of heavy metals and pesticides in irrigated rice cultivars near industrial areas of Dhaka, Bangladesh - Muhammad Nurul Huda; Mohammad Harun-Ur-Rashid; Anowar Hosen; Mahafuga Akter; Md. Mominul Islam; Sharmin Zaman Emon; Asma Rahman; Zuairia Binte Jashim; Saif Shahrukh; Mohammad Ismail (Environmental Monitoring and Assessment, 2024)

Polycyclic aromatic hydrocarbons in ship breaking area and associated ecological risk assessment: evidence from the Sitakund ship-breaking area in Bangladesh - Suman Barua; Rajesh Mutsuddi; Sabrina Sultana; Md. Samrat Mohay Menul Islam; Suman Das; Mohammad Mostafa; Dipankar Chakraborty; Ismail M. M. Rahman (Environmental Science and Pollution Research, 2024)

Simultaneous removal of Ni2+ and Congo red from wastewater by crystalline nanocellulose - Modified coal bionanocomposites: Continuous adsorption study with mathematical modeling - Md. Mahmudur Rahman; Md. Aftab Ali Shaikh; Mst. Sarmina Yeasmin; Md. Abdul Gafur; Md. Ismail Hossain; Md. Ashraful Alam; Md. Salim Khan; Trisha Paul; Md. Saiful Quddus (Groundwater for Sustainable Development, 2024)

Polygonum minus: A tropical medicinal herb with vast applications in food, agricultural, and medicinal fields - Zhongming Yang; Xi Deng; Zhongguo Yang; Mingzhao Han; Norsharina Ismail; Kim Wei Chan; Ahmad Faizal Abdull Razis; Norhaizan Mohd Esa; Ket Li Ho; Md Zuki Abu Bakar (Food Bioscience, 2024)

Advancement in modern breeding and genomic approaches to accelerate rice improvement: speed breeding focus - Fatin’Alyaa Zainuddin; Mohd Razi Ismail; Muhammad Asyraf Md Hatta; Shairul Izan Ramlee (Euphytica, 2024)

Empowered machine learning algorithm to identify sustainable groundwater potential zone map in Jashore District, Bangladesh - Sujit Kumar Roy; Md. Mahmudul Hasan; Ismail Mondal; Javed Akhter; Sonzet Kumar Roy; Swapan Talukder; A.K.M. Saiful Islam; Atiqur Rahman; Shankar Karuppannan (Groundwater for Sustainable Development, 2024)

Appraisal of macro elements and trace metals in the edible fish from the Black Sea connecting coastal river, Türkiye: A preliminary study for health risk assessment - Fikret Ustaoğlu; Md. Humayun Kabir; Tapos Kormoker; Zulhilmi Ismail; Md. Saiful Islam; Beyhan Taş; Halim Topaldemir (Regional Studies in Marine Science, 2024)

WITHDRAWN: Trace metals translocation from soil to plants: Health risk assessment via consumption of vegetables in the urban sprawl of a developing country - KM Shamsul Haque; Md Saiful Islam; Sujat Ahmed; Md Zillur Rahman; Debolina Halder Hemy; Md Towhidul Islam; Md Kamal Hossain; Md Rafiq Uddin; Abu Reza Md Towfiqul Islam; Md Yousuf Mia; Zulhilmi Ismail; Abdullah Al Bakky; et al. (Food and Chemical Toxicology, 2024)

A case of rotenone poisoning from ingesting Derris trifoliata Lour. (Tuba fruit/pod) in Malaysia - Si Ling Yeoh; Pheik Sian Choong; Rahmad Zakaria; Nur Azzalia Kamaruzaman; Sazaroni Md Rashid; Mohd Fadhli Razali; Ahmad Khaldun Ismail (Toxicon, 2024)

Contamination and ecological risk assessment of Cr, As, Cd and Pb in water and sediment of the southeastern Bay of Bengal coast in a developing country - Md. Saiful Islam; Md. Towhidul Islam; Uttam Biswas Antu; Md. Sadik Mahmud Saikat; Zulhilmi Ismail; Shamsuddin Shahid; Abu Reza Md. Towfiqul Islam; Mir Mohammad Ali; Abdullah Al Bakky; Sujat Ahmed; Khalid A. Ibrahim; Rahmah N. Al-Qthanin; et al. (Marine Pollution Bulletin, 2023)

Oncoinformatic screening of the gene clusters involved in the HER2-positive breast cancer formation along with the in silico pharmacodynamic profiling of selective long-chain omega-3 fatty acids as the metastatic antagonists - A K M Helal Morshed; Salauddin Al Azad; Md. Abdur Rashid Mia; Mohammad Fahim Uddin; Tanzila Ismail Ema; Rukaiya Binte Yeasin; Sanjida Ahmed Srishti; Pallab Sarker; Rubaita Younus Aurthi; Farhan Jamil; Nure Sharaf Nower Samia; Partha Biswas; et al. (Molecular Diversity, 2023)

Computer Vision and Image Processing Approaches for Corrosion Detection - Ahmad Ali Imran Mohd Ali; Shahrizan Jamaludin; Md Mahadi Hasan Imran; Ahmad Faisal Mohamad Ayob; Sayyid Zainal Abidin Syed Ahmad; Mohd Faizal Ali Akhbar; Mohammed Ismail Russtam Suhrab; Mohamad Riduan Ramli (Journal of Marine Science and Engineering, 2023)
Corrosion is an undesirable phenomenon resulting in material deterioration and degradation through electrochemical or chemical reactions with the surrounding environment. Additionally, corrosion presents considerable threats in both the short and long term because of its ability to create failures, leakages, and damage to materials, equipment, and environment. Despite swift technological developments, it remains difficult to determine the degrees of corrosion due to the different textures and the edgeless boundary of corrosion surfaces. Hence, there is a need to investigate the robust corrosion detection algorithms that are suitable for all degrees of corrosion. Recently, many computer vision and image processing algorithms have been developed for corrosion prediction, assessment, and detection, such as filtering, texture, color, pixelation, image enhancement, wavelet transformation, segmentation, classification, and clustering approaches. As a result, this paper reviews and discusses the state-of-the-art computer vision and image processing methods that have been developed for corrosion detection in various applications, industries, and academic research. The challenges for corrosion detection using computer vision and image processing algorithms are also explored. Finally, recommendations for future research are also detailed.

Survey on sea snakebite and related morbidity and mortality among Bangladeshi fishermen in the Bay of Bengal: A pilot study - Aniruddha Ghose; Muhammed Syedul Alam; Abdullah Abu Sayeed; Mohammed Shah Jahan; Fateha Akter; Rabiul Alam Md Erfan Uddin; Shoman Sarkar; A.S.M. Zahed; Kajal Kanti Das; Md Habibur Rahman; Rumana Rashid; Hasina Nasrin; et al. (Toxicon, 2023)

Prophylactic effects of dietary Isochrysis galbana on immersion-challenged red hybrid tilapia (Oreochromis spp.) with Streptococcus agalactiae by spleen-NMR-metabolomics - Muhammad Safwan Ahamad Bustamam; Khozirah Shaari; Chong Chou Min; Md Shirajum Monir; Hamza Ahmed Pantami; Intan Safinar Ismail (Aquaculture International, 2023)

Spatial assessment of the seasonal impact of brickfields on air pollution in Dhaka metropolitan area using ordination techniques - Maisha Mahboob; Monojit Saha; Md Ismail Hossain (Air Quality, Atmosphere & Health, 2023)

Natural flavonoids effectively block the CD81 receptor of hepatocytes and inhibit HCV infection: a computational drug development approach - Dipta Dey; Partha Biswas; Priyanka Paul; Shafi Mahmud; Tanzila Ismail Ema; Arysha Alif Khan; Shahlaa Zernaz Ahmed; Mohammad Mehedi Hasan; Abu Saim Mohammad Saikat; Babry Fatema; Shabana Bibi; Md. Ataur Rahman; et al. (Molecular Diversity, 2023)

Amentoflavone derivatives significantly act towards the main protease (3CLPRO/MPRO) of SARS-CoV-2: in silico admet profiling, molecular docking, molecular dynamics simulation, network pharmacology - Dipta Dey; Rajib Hossain; Partha Biswas; Priyanka Paul; Md. Aminul Islam; Tanzila Ismail Ema; Bibhuti Kumar Gain; Mohammad Mehedi Hasan; Shabana Bibi; Muhammad Torequl Islam; Md. Ataur Rahman; Bonglee Kim (Molecular Diversity, 2023)

A case of fatal envenomation by a captive puff adder (Bitis arietans) in Malaysia - Zulfahimi Husain; Aji Caesar Wicaksono; Asyhok Renault; Siti Sarah Md Zhahir; Ahmad Khaldun Ismail (Toxicon, 2023)

Future Köppen-Geiger climate zones over Southeast Asia using CMIP6 Multimodel Ensemble - Mohammed Magdy Hamed; Mohamed Salem Nashwan; Shamsuddin Shahid; Xiao-Jun Wang; Tarmizi Bin Ismail; Ashraf Dewan; Md Asaduzzaman (Atmospheric Research, 2023)

Application of Artificial Intelligence in Marine Corrosion Prediction and Detection - Md Mahadi Hasan Imran; Shahrizan Jamaludin; Ahmad Faisal Mohamad Ayob; Ahmad Ali Imran Mohd Ali; Sayyid Zainal Abidin Syed Ahmad; Mohd Faizal Ali Akhbar; Mohammed Ismail Russtam Suhrab; Nasharuddin Zainal; Syamimi Mohd Norzeli; Saiful Bahri Mohamed (Journal of Marine Science and Engineering, 2023)
One of the biggest problems the maritime industry is currently experiencing is corrosion, resulting in short and long-term damages. Early prediction and proper corrosion monitoring can reduce economic losses. Traditional approaches used in corrosion prediction and detection are time-consuming and challenging to execute in inaccessible areas. Due to these reasons, artificial intelligence-based algorithms have become the most popular tools for researchers. This study discusses state-of-the-art artificial intelligence (AI) methods for marine-related corrosion prediction and detection: (1) predictive maintenance approaches and (2) computer vision and image processing approaches. Furthermore, a brief description of AI is described. The outcomes of this review will bring forward new knowledge about AI and the development of prediction models which can avoid unexpected failures during corrosion detection and maintenance. Moreover, it will expand the understanding of computer vision and image processing approaches for accurately detecting corrosion in images and videos.

50 years of rice breeding in Bangladesh: genetic yield trends - Niaz Md. Farhat Rahman; Waqas Ahmed Malik; Md. Shahjahan Kabir; Md. Azizul Baten; Md. Ismail Hossain; Debi Narayan Rudra Paul; Rokib Ahmed; Partha Sarathi Biswas; Md. Chhiddikur Rahman; Md. Sazzadur Rahman; Khandakar Md. Iftekharuddaula; Steffen Hadasch; et al. (Theoretical and Applied Genetics, 2023)
To assess the efficiency of genetic improvement programs, it is essential to assess the genetic trend in long-term data. The present study estimates the genetic trends for grain yield of rice varieties released between 1970 and 2020 by the Bangladesh Rice Research Institute. The yield of the varieties was assessed from 2001–2002 to 2020–2021 in multi-locations trials. In such a series of trials, yield may increase over time due to (i) genetic improvement (genetic trend) and (ii) improved management or favorable climate change (agronomic/non-genetic trend). In both the winter and monsoon seasons, we observed positive genetic and non-genetic trends. The annual genetic trend for grain yield in both winter and monsoon rice varieties was 0.01 t ha −1 , while the non-genetic trend for both seasons was 0.02 t ha −1 , corresponding to yearly genetic gains of 0.28% and 0.18% in winter and monsoon seasons, respectively. The overall percentage yield change from 1970 until 2020 for winter rice was 40.96%, of which 13.91% was genetic trend and 27.05% was non-genetic. For the monsoon season, the overall percentage change from 1973 until 2020 was 38.39%, of which genetic and non-genetic increases were 8.36% and 30.03%, respectively. Overall, the contribution of non-genetic trend is larger than genetic trend both for winter and monsoon seasons. These results suggest that limited progress has been made in improving yield in Bangladeshi rice breeding programs over the last 50 years. Breeding programs need to be modernized to deliver sufficient genetic gains in the future to sustain Bangladeshi food security.

Projecting spatiotemporal changes of precipitation and temperature in Iraq for different shared socioeconomic pathways with selected Coupled Model Intercomparison Project Phase 6 - Saleem A. Salman; Mohammed Magdy Hamed; Shamsuddin Shahid; Kamal Ahmed; Ahmad Sharafati; Md. Asaduzzaman; Ghaith Falah Ziarh; Tarmizi Ismail; ‪Eun‐Sung Chung; Xiao‐Jun Wang; Ashraf Dewan (International Journal of Climatology, 2022)
Changes in precipitation and temperature have crucial implications in the arid region due to their fragile environment. This study was an attempt to estimate possible spatiotemporal alteration of annual and seasonal precipitation and temperature in Iraq. Statistical downscaling of Coupled Model Intercomparison Project Phase 6 (CMIP6) global climate model (GCM) simulations for different shared socioeconomic pathways (SSP) was utilized. The GCMs were ranked according to their skills in simulating climate research unit (CRU) precipitation and temperature climatology along with their seasonality. Nonlocal model output statistics (MOS) models were implemented using a support vector machine (SVM) for downscaling and projection of selected GCM precipitation and temperature. Results revealed ACCESS‐CM2, BCC‐CSM2‐MR, GISS‐E2‐1‐G and MRI‐ESM2‐0 GCMs are most suitable for Iraq. The spatiotemporal changes in precipitation indicated a substantial decrease to north (up to −7.8%·mm −1 ) while an increase (around 3.0%) to south for different SSPs. Far future (2060–2099) showed both increase and decrease in precipitation than near future (2020–2059). The precipitation was projected to reduce in winter and increase in summer for all climate zones during both periods. The maximum temperature was projected to increase by 4.5°C to the north and 0.9–2°C to the south. In contrast, the minimum temperature was projected to rise by 1.0–3.5°C to both north and south. Both maximum and minimum temperatures may increase; however, more increases might be in winter and less in summer. The minimum temperature increase will be higher than the maximum temperature in the cold northern region and vice versa. Uncertainty in precipitation and temperature projections was higher for the far‐future period with higher SSPs than for the near‐future period with lower SSPs. The results of this study can guide the development of strategic policies for climate resiliency development in Iraq.

Determinants of households’ livelihood diversification strategies to adapt to natural hazards: evidence from ecologically vulnerable haor region of Bangladesh - Mohammad Shamsul Hoq; Md. Taj Uddin; Shankar Kumar Raha; Mohammad Ismail Hossain (Natural Hazards, 2022)

Thermal bioclimatic indicators over Southeast Asia: present status and future projection using CMIP6 - Mohammed Magdy Hamed; Mohamed Salem Nashwan; Shamsuddin Shahid; Tarmizi bin Ismail; Ashraf Dewan; Md Asaduzzaman (Environmental Science and Pollution Research, 2022)

The antiproliferative and apoptotic potential of Clinacanthus nutans against human breast cancer cells through targeted apoptosis pathway - Noor Zafirah Ismail; Salwani Md Saad; Ismail Abiola Adebayo; Zaleha Md Toha; Rafedah Abas; Nur Nadhirah Mohamad Zain; Hasni Arsad (Environmental Science and Pollution Research, 2022)

Does the US regional greenhouse gas initiative affect green innovation? - Md Azizur Rahman; Rubi Ahmad; Izlin Ismail (Environmental Science and Pollution Research, 2022)

Classification of weed using machine learning techniques: a review—challenges, current and future potential techniques - Ahmed Husham Al-Badri; Nor Azman Ismail; Khamael Al-Dulaimi; Ghalib Ahmed Salman; A. R. Khan; Aiman Al-Sabaawi; Md Sah Hj Salam (Journal of Plant Diseases and Protection, 2022)

Spread of the invasive Javan myna along an urban–suburban gradient in Peninsular Malaysia - Fatihah Najihah Arazmi; Nor Adibah Ismail; Ummi Nur Syafiqah Daud; Kamaruddin Zainul Abidin; Shukor Md Nor; Mohammad Saiful Mansor (Urban Ecosystems, 2022)

Status, Biodiversity, and Ecosystem Services of Seagrass Habitats Within the Coral Triangle in the Western Pacific Ocean - Abdulla- Al-Asif; Abu Hena Mustafa Kamal; Hadi Hamli; Mohd Hanafi Idris; Geoffery James Gerusu; Johan Ismail; Md Khurshid Alam Bhuiyan; Muyassar H. Abualreesh; Najiah Musa; Mohd Effendy Abd Wahid; Manoranjan Mishra (Ocean Science Journal, 2022)

Coral health assessment in Malaysia: a case study of Pulau Anak Datai, Langkawi - Mohamad Saupi Ismail; Zaidnuddin Ilias; Md. Nizam Ismail; Gerald B. Goeden; Chee Kong Yap; Khalid Awadh Al-Mutairi; Salman Abdo Al-Shami (Environmental Science and Pollution Research, 2022)

Spatiotemporal trends of temperature extremes in Bangladesh under changing climate using multi-statistical techniques - Javed Mallick; Abu Reza Md. Towfiqul Islam; Bonosri Ghose; H. M. Touhidul Islam; Yousuf Rana; Zhenghua Hu; Shakeel Ahmed Bhat; Subodh Chandra Pal; Zulhilmi Bin Ismail (Theoretical and Applied Climatology, 2022)

Influence of physico-chemical characteristics of rembau river, peninsular Malaysia, on congregating Pteroptyx fireflies - Nur-Athirah Abdullah; Lailatul-Nadhirah Asri; Shahril Mod Husin; Aisah Md Shukor; Nurul Darsani Ahmad Darbis; Kamaruzzaman Ismail; Hani Kartini Agustar; Norela Sulaiman; Izfa Riza Hazmi (Environmental Monitoring and Assessment, 2021)

Non-coding Single Nucleotide Variants of Renin and the (Pro)renin Receptor are Associated with Polygenic Diseases in a Bangladeshi Population - Jobaida Akther; Ashish Das; Md Arifur Rahman; Sajoy Kanti Saha; Md Ismail Hosen; Akio Ebihara; Tsutomu Nakagawa; Fumiaki Suzuki; A. H. M. Nurun Nabi (Biochemical Genetics, 2021)

Electroflotation treatment of stabilized landfill leachate using titanium-based electrode - A. M. H. Shadi; M. A. Kamaruddin; N. M. Niza; M. I. Emmanuel; Md. S. Hossain; N. Ismail (International Journal of Environmental Science and Technology, 2021)

Ranking of gridded precipitation datasets by merging compromise programming and global performance index: a case study of the Amu Darya basin - Obaidullah Salehie; Tarmizi Ismail; Shamsuddin Shahid; Kamal Ahmed; S Adarsh; Md Asaduzzaman; Ashraf Dewan (Theoretical and Applied Climatology, 2021)

Bacterial Count and Proximate Composition of an Indian sub-continental Freshwater Barb, Punti ( Puntius sophore ) and a Gangetic Catfish, Gulsha ( Mystus cavasius ) during Drying-up Process - Md. Nurul Haider; Sangita Bhattacharjee; Fatema Hoque Shikha; Ismail Hossain (Journal of Aquatic Food Product Technology, 2021)

Hydrogeological characterization of saline water aquifer deploying multiple well logs at Khulna, a coastal region of Bangladesh - Md Ismail Hossain; Md Moklesur Rahman; Md Ibrahim Khalil; Faisal Kabir Riday; Mehedi Hassan Shetol; Ratneshwar Sarder; Md Golam Rasul; Md Zafrul Kabir; Md Shafiqul Islam (Arabian Journal of Geosciences, 2021)

Association study of leukocyte telomere length and genetic polymorphism within hTERT promoter with type 2 diabetes in Bangladeshi population - Atoll Goswami; Nafiul Huda; Tahirah Yasmin; Md. Ismail Hosen; A. K. M. Mahbub Hasan; A. H. M. Nurun Nabi (Molecular Biology Reports, 2021)

Incorporation of Smooth Muscle Cells Derived from Human Adipose Stem Cells on Poly(Lactic-co-Glycolic Acid) Scaffold for the Reconstruction of Subtotally Resected Urinary Bladder in Athymic Rats - Salah Abood Salem; Zahra Rashidbenam; Mohd Hafidzul Jasman; Christopher Chee Kong Ho; Ismail Sagap; Rajesh Singh; Mohd Reusmaazran Yusof; Zulkifli Md. Zainuddin; Ruszymah Bt Haji Idrus; Min Hwei Ng (Tissue Engineering and Regenerative Medicine, 2020)

Laboratory air quality and microbiological contamination in a university building - Siti Amira ‘Ainaa’ Idris; Marlia M. Hanafiah; Marzuki Ismail; Samsuri Abdullah; Md Firoz Khan (Arabian Journal of Geosciences, 2020)

TiO2 Coated-Asphalt Buton Photocatalyst for High-Performance Motor Vehicles Gas Emission Mitigation - Muhammad Zakir Muzakkar; Muhammad Nurdin; Ima Ismail; Maulidiyah Maulidiyah; Dwiprayogo Wibowo; Ratna Ratna; Siti Khatijah Md Saad; Akrajas Ali Umar (Emission Control Science and Technology, 2020)

Cryopreservation of spermatozoa on grouper species: a review - Che Ismail Che‐Zulkifli; Ivan Chong Chu Koh; Md Sheriff Shahreza; Mhd Ikhwanuddin (Reviews in Aquaculture, 2020)
Cryopreservation of spermatozoa of grouper species supporting artificial insemination in production of fry has contributed to the grouper aquaculture industry. Grouper is a high‐value species in marine cage finfish culture and a major business for the aquaculture industry in South East Asia. The species contributes a significant value to the income of South East Asian countries such as Indonesia, Malaysia, Philippines and Thailand. Hybrid grouper is a new candidate for marine finfish culture, and cryopreservation of grouper and giant grouper spermatozoa is important to support development of its production. This review article discusses the cryopreservation of the spermatozoa of grouper species specifically. Emphasis is placed on the protocols for implementation and implications of the cryopreservation of grouper spermatozoa in the marine finfish aquaculture industry.

Matrix Production in Chondrocytes Transfected with Sex Determining Region Y-Box 9 and Telomerase Reverse Transcriptase Genes: An In Vitro Evaluation from Monolayer Culture to Three-Dimensional Culture - Noorhidayah Md Nazir; Ahmad Hafiz Zulkifly; Kamarul Ariffin Khalid; Ismail Zainol; Zaitunnatakhin Zamli; Munirah Sha’ban (Tissue Engineering and Regenerative Medicine, 2019)

Geochemistry of subsurface Late Quaternary ironstones in Rajshahi and Bogra Districts, Bangladesh: implications for genetic and depositional conditions - Md. Sazzadur Rahman; Ismail Hossain; Pradip Kumar Biswas; Md. Abdur Rahim; A. S. M. Mehedi Hasan; Md. Ibrahim Adham (Acta Geochimica, 2019)

Correction to: Functional Polymorphism Located in the microRNA Binding Site of the Insulin Receptor (INSR) Gene Confers Risk for Type 2 Diabetes Mellitus in the Bangladeshi Population - Mahrima Parvin; Farhana Jahan; Pankaj Kumar Sarkar; Zakir Hossain Howlader; A. H. M. Nurun Nabi; Md. Ismail Hosen (Biochemical Genetics, 2019)

Functional Polymorphism Located in the microRNA Binding Site of the Insulin Receptor (INSR) Gene Confers Risk for Type 2 Diabetes Mellitus in the Bangladeshi Population - Mahrima Parvin; Farhana Jahan; Pankaj Kumar Sarkar; Zakir Hossain Howlader; A. H. M. Nurun Nabi; Md. Ismail Hosen (Biochemical Genetics, 2019)

FEG-EPMA mapping and Fe-Ti oxide mineral chemistry of Brahmaputra River sediments in Bangladesh: provenance and petrogenetic implications - A. S. M. Mehedi Hasan; Ismail Hossain; Md. Aminur Rahman; Md. Sazzadur Rahman; Mohammad Nazim Zaman; Pradip Kumar Biswas (Arabian Journal of Geosciences, 2018)

Suppression of PGE2 production via disruption of MAPK phosphorylation by unsymmetrical dicarbonyl curcumin derivatives - Mohd Fadhlizil Fasihi Mohd Aluwi; Kamal Rullah; Md. Areeful Haque; Bohari M. Yamin; Waqas Ahmad; Muhammad Wahab Amjad; Sze Wei Leong; Nurul Amira Fahmizar; Juriyati Jalil; Faridah Abas; Nor Hadiani Ismail; Ibrahim Jantan; et al. (Medicinal Chemistry Research, 2017)

Mangrove Macroalgae as Biomonitors of Heavy Metal Contamination in a Tropical Estuary, Malaysia - Md Masum Billah; Abu Hena Mustafa Kamal; Mohd Hanafi Idris; Johan Ismail (Water, Air, & Soil Pollution, 2017)

Detecting medicinal plants species using GPS positioning in Vidyasagar University Campus, Midnapore, West Bengal, India - Sk. Md. Abu Imam Saadi; Ismail Mondal; Subrata Sarkar; Amal Kumar Mondal; Jatisankar Bandyopadhyay (Spatial Information Research, 2017)

Neuroprotective Effect of Magnesium Acetyltaurate Against NMDA-Induced Excitotoxicity in Rat Retina - Lidawani Lambuk; Azliana Jusnida Ahmad Jafri; Natasha Najwa Nor Arfuzir; Igor Iezhitsa; Renu Agarwal; Khairul Nizam Bin Rozali; Puneet Agarwal; Nor Salmah Bakar; Methil Kannan Kutty; Ahmad Pauzi Md. Yusof; Anna Krasilnikova; Alexander Spasov; et al. (Neurotoxicity Research, 2017)

Development of Tide–Surge Interaction Model for the Coastal Region of Bangladesh - Gour Chandra Paul; Ahmad Izani Md. Ismail; Azizur Rahman; Md. Fazlul Karim; Ashabul Hoque (Estuaries and Coasts, 2016)

New sources of resistance to Cucumber mosaic virus in Capsicum annuum - Md. Siddiqur Rahman; Abdul Mannan Akanda; Ismail Hossain Mian; Md. Khurshed Alam Bhuiyan; Md. Motaher Hossain (Journal of Crop Science and Biotechnology, 2016)

Construction and analysis of an Oryza sativa (cv. MR219) salinity-related cDNA library - Poya Hedayati; Hossein Hosseni Monfard; Nurulhikma Md Isa; Duk Ju Hwang; Che Radziah Che Mohd Zain; Md. Imtiaz Uddin; Ab Rahman Zuraida; Ismanizan Ismail; Zamri Zainal (Acta Physiologiae Plantarum, 2015)

Implementation of method of lines to predict water levels due to a storm along the coastal region of Bangladesh - Gour Chandra Paul; Ahmad Izani Md. Ismail; Md. Fazlul Karim (Journal of Oceanography, 2014)

Application of a subtractive genomics approach for in silico identification and characterization of novel drug targets in Mycobacterium tuberculosis F11 - Md. Ismail Hosen; Arif Mohammad Tanmoy; Deena-Al Mahbuba; Umme Salma; Mohammad Nazim; Md. Tariqul Islam; Sharif Akhteruzzaman (Interdisciplinary Sciences: Computational Life Sciences, 2014)

Exploring Cancer Development in Adulthood: Cholinesterase Depression and Genotoxic Effect From Chronic Exposure to Organophosphate Pesticides Among Rural Farm Children - Vivien How; Zailina Hashim; Patimah Ismail; Salmiah Md Said; Dzolkhifli Omar; Shamsul Bahri Mohd Tamrin (Journal of Agromedicine, 2014)

Levels of heavy metals in tissues of shingi fish (Heteropneustes fossilis) from Buriganga River, Bangladesh - Aleya Begum; Ahmed Ismail Mustafa; Md. Nurul Amin; Tasrina Rabia Chowdhury; Shamshad Begum Quraishi; Nasrin Banu (Environmental Monitoring and Assessment, 2013)

Free Convection of Non-Newtonian Nanofluids in Porous media with Gyrotactic Microorganisms - W. A. Khan; Md. Jashim Uddin; A. I. Md. Ismail (Transport in Porous Media, 2013)

Structural, functional and molecular docking study to characterize GMI1 from Arabidopsis thaliana - Md. Rezaul Islam; Md. Ismail Hosen; Aubhishek Zaman; Md. Ohedul Islam (Interdisciplinary Sciences: Computational Life Sciences, 2013)

Contribution of offshore islands in the prediction of water levels due to tide–surge interaction for the coastal region of Bangladesh - Gour Chandra Paul; Ahmad Izani Md. Ismail (Natural Hazards, 2013)

Free Convection Boundary Layer Flow from a Heated Upward Facing Horizontal Flat Plate Embedded in a Porous Medium Filled by a Nanofluid with Convective Boundary Condition - Md. Jashim Uddin; W. A. Khan; A. I. Md. Ismail (Transport in Porous Media, 2012)

Sustainability of Groundwater Resources in the North-Eastern Region of Bangladesh - Md Hossain Ali; Ismail Abustan; Md Ashiqur Rahman; Abu Ahmed Mokammel Haque (Water Resources Management, 2012)

A mutant l-asparaginase II signal peptide improves the secretion of recombinant cyclodextrin glucanotransferase and the viability of Escherichia coli - Noor Faizah Ismail; Salehhuddin Hamdan; Nor Muhammad Mahadi; Abdul Munir Abdul Murad; Amir Rabu; Farah Diba Abu Bakar; Peter Klappa; Rosli Md. Illias (Biotechnology Letters, 2011)

Stagnant surface water bodies (SSWBs) as an alternative water resource for the Chittagong metropolitan area of Bangladesh: physicochemical characterization in terms of water quality indices - Ismail Md. Mofizur Rahman; M. Monirul Islam; M. Mosharraf Hossain; M. Shahadat Hossain; Zinnat A. Begum; Didarul A. Chowdhury; Milan K. Chakraborty; M. Azizur Rahman; M. Nazimuddin; Hiroshi Hasegawa (Environmental Monitoring and Assessment, 2011)

Management of palm oil mill effluent through production of cellulases by filamentous fungi - Shah Samiur Rashid; Md. Zahangir Alam; M. Ismail A. Karim; M. Hamzah Salleh (World Journal of Microbiology and Biotechnology, 2009)